Analyzing the Brazilian Anti-Freire Movement Through Freire’s Framework - Yano, Vitor (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2025)
Paulo Freire is considered one of the world’s most notable thinkers in the field of education. Even so, an increasing political polarization in Brazil, his home country, led to the development of a movement against him and his work. In this essay, I analyzed the Brazilian anti-Freire movement using his framework, as an imaginative exercise of a dialogue between him and its arguments. For that, I reviewed the main discourses of the movement and, through content analysis, categorized them in three categories: ideological disagreement, contradiction, and groundless. Next, I analyzed the arguments, relying on Freire’s theories. I concluded that this phenomenon ends up confirming his theories. The resistance to changes in the traditional educational system reflects his concept of fear of freedom. For the oppressors, his pedagogy is dangerous for threatening their position of power. Furthermore, while the oppressed reproduce the dominant ideology, they are part of this reactionary movement.